180 Retrograde Hindfoot Nailing for the Treatment of Acute Ankle Fractures in the Elderly - a Systematic Review and Meta-Analysis. (19th August 2022) - Lu, V; Tennyson, M; Zhou, A; Fortune, M; Thahir, A; Krkovic, M
Abstract: Aim: Fragility ankle fractures are traditionally managed conservatively or with open reduction internal fixation (ORIF). Tibiotalocalcaneal (TTC) nailing is an alternative option for the geriatric patient. This meta-analysis provides the most detailed analysis of hindfoot nailing for fragility ankle fractures. Method: A systematic search was performed on MEDLINE, EMBASE, Cochrane Library, Scopus, Web of Science, identifying fourteen studies for inclusion. Studies including patients over 60 with a fragility ankle fracture, treated with TTC nail were included. Patients with a previous fracture of the ipsilateral limb, fibular nails, and pathological fractures were excluded. Meta-regression analyses were performed to explore sources of heterogeneity, and publication bias was assessed using Egger's test. Results: 312 ankle fractures were included. The mean age was 77.3 (32–101) years. 26.9% were male, and 41.9% were diabetics. The pooled proportion of superficial infection, deep infection, implant failure, malunion, and all-cause mortality was 0.10 (95%CI:0.06–0.16; I 2 =44%), 0.08 (95%CI:0.06–0.11, I 2 =0%), 0.11 (95%CI:0.07–0.15, I 2 =0%), 0.11 (95%CI:0.06–0.18; I 2 =51%), and 0.27 (95%CI:0.20–0.34; I 2 =11%), respectively. The pooled mean post-operative OMAS score was 54.07 (95%CI:48.98–59.16; I 2 =85%). The best-fitting meta-regression model included age and percentage of male patients as covariates (p=0.0263), and were inversely correlated with higher OMAS scores. Egger's test (p=0.56) showed no significant publication bias. Conclusions: TTC nailing is an adequate alternative option for fragility ankle fracture management. However, current evidence includes mainly case series with inconsistent outcome measures reported and post-operative rehabilitation protocols. Prospective RCTs with long follow-up times and large cohort sizes are needed to clearly guide the use of TTC nailing for ankle fractures.